Alcohol dependence severity determines the course of treatment‐seeking patients. (29th September 2021) - Yoshimura, Atsushi; Kimura, Mitsuru; Matsushita, Sachio; Yoneda, Jun‐ichi; Maesato, Hitoshi; Komoto, Yasunobu; Nakayama, Hideki; Sakuma, Hiroshi; Yumoto, Yosuke; Takimura, Tsuyoshi; Tohyama, Tomomi; Iwahara, Chie; et al.
Abstract: Background: While accumulating evidence suggests a relation between the severity of alcohol dependence and the risk of its recurrence, the impact of dependence severity on the course of the disorder has not been carefully evaluated. The present study examined the impact of several severity indices of alcohol dependence on the drinking course after inpatient treatment. Methods: This prospective study was conducted over a 12‐month period following alcohol treatment at a specialized hospital. A total of 712 consecutively admitted alcohol‐dependent patients were targeted for enrollment at the time of their hospitalization, with 637 patients registered and followed. The characteristics and severity of the subjects were assessed using multiple methods at admission, with their course after discharge followed continuously using mailed questionnaires that queried them regarding their drinking behavior. Results: Greater severity of dependence, assessed using the number of ICD‐10 diagnostic criteria met, was associated with a lower rate of abstinence during the study period ( p  = 0.035). The rate of abstinence also decreased significantly as the baseline blood gamma‐glutamyl transferase value and Alcohol Dependence Scale (ADS) score increased ( p  = 0.031 and p  = 0.0002, respectively). In multivariate Cox proportional hazards analyses, the group with the most severe ADS scores had a significantly greater risk of relapse to drinking than the group with the least severe scores (HR = 2.67, p  = 0.001). Dependence severity also associated with the drinking pattern; participants in both the controlled drinking group and the abstinence group had lower ADS scores at admission and a later age at first drinking ( p  = 0.001 and p  < 0.001, respectively) than those with poorer drinking outcomes. Conclusions: The present study showed that more severe alcohol dependence predicts a poorer course after alcohol treatment, as reflected by findings on multiple measures. These results suggest that assessing the dependence severity at the outset of treatment could be useful both in predicting treatment outcome and targeting interventions to alcohol‐dependent individuals who need additional support in their recovery. Abstract : The present prospective study showed that severe alcohol dependence predicted a poorer course after alcohol treatment from different viewpoints. The endorsed number in ICD‐10 diagnostic criteria, blood GGT value and Alcohol Dependence Scale (ADS) score at admission were associated with lower abstinence rates during the 12 months following discharge. These severity indices predicted not only the likelihood of abstinence, but also the drinking pattern. As the ADS severity level increased, the hazard ratios of relapse drinking also increased in multivariate hazards analyses.